Il saccheggio nazista dell'arte europea Uno Sguardo Comparatistico sul Contenzioso Transnazionale nei Restitution Cases - Solaro, Livia (FrancoAngeli, 2022)
Throughout World War II, it is estimated that up to 20% of all of Europe's art became the object of numerous forms of looting by the Nazi regime. Despite the Allies' significant efforts to recover and return such artworks, the repercussions of this unprecedented plunder can still be observed to this day; at the turn of the millennium, a renewed interest in the tragic fate of the looted art that was never recovered pervaded the Western world, leading to a new wave of restitutions that does not appear bound to come to a halt anytime soon. This volume highlights the fundamental differences that have characterized the evolution of this process in Europe and in the Unites States, by retracing some landmark cases and the way they have impacted the discussion around restitution.